A new L-glutaminase from Kosakonia sp.: extracellular production, gene identification and structural analysis - Aizi Nor Mazila, Ramli; Nur Dini, Johari; Mohd Akmal, Azhar; Rohaida, Che Man; Hazrulrizawati, Hamid (Springer International Publishing, 2021)
A comprehensive research has been carried out on L-glutaminase producers from marine bacteria. Among the evaluated isolates, Kosakonia radicincitans was found to be a L-glutaminase producer from a marine environment, having the highest enzymatic activities. The optimal condition for L-glutaminase production from K. radicincitans was at pH and temperature of 7.0 and 37 °C, respectively. The enzyme was found stable between pH 4 and 8 and its function also maintained at temperatures between 31 and 43 °C after 30-min incubation. Both the amino acid sequence and domain analysis of the L-glutaminase from the Kosakonia strains revealed various similarities and dissimilarities between these amidase enzymes. Sequence analysis and comparison of L-glutaminase from Kosakonia sp. with other L-glutaminase along with structural prediction were able to identify the unique characteristics of the predicted structures and offer a different perspective into their distinguishable properties for industrial use.